Keragaman Bakteri Endofit Penghasil L-Asparaginase Bebas L-Glutaminase - sulistiyani, tri ratna; kusumawati, dinihari indah (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2019)
Endophytes are potential as a source of active compound producer. Endophytes that is isolated from tropical medicinal plants has been getting attention due to its high biodiversity and active compound producing ability. L-asparaginase is the first enzyme used as chemotherapeutic agent for leukemia. The aim of this study is to collect the endophytic bacteria associated with tropical medicinal plants from Sumba Island and investigate the activity of L-asparaginase without L-glutaminase from endophytic bacteria isolates. The samples Gliricidia sepium, Pittosporum moluccanum, Clerodendrum buchanani, and Zingiberaceae are collected from Wanggameti, East Sumba, NTT. Samples are sterilized using surface-sterilization method and endophytic bacteria are isolated using plant piece method on R2A media. Selected endophytic bacteria are identified by 16S rDNA sequences. L-asparaginase screening is conducted using modified R2A with addition of L-asparagine and phenol red as colour indicator. A total of 34 isolates of endophytic bacteria were collected from 5 samples. A total of 14 genus consisted of 17 different bacterial species were obtained from 34 selected isolates. Endophytic bacteria of P. stutzeri strains of SMKL1 and R. radiobacter strains of SMKW2 from the Kahili plant were needed as L-glutaminase-free L-asparaginase and were potential to be candidate of leukemia cancer chemotherapy